2018
DOI: 10.1111/jar.12532
|View full text |Cite
|
Sign up to set email alerts
|

The GO4KIDDS School Satisfaction Scale

Abstract: Results support reliability and validity, making the proposed scale valuable for survey research investigating school satisfaction among parents of children with DD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The GO4KIDDS School Satisfaction Scale (Perry et al, 2018) has demonstrated preliminary criterion-related validity (Perry et al, 2018). The mean score was used as the main dependent measure.…”
Section: School Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GO4KIDDS School Satisfaction Scale (Perry et al, 2018) has demonstrated preliminary criterion-related validity (Perry et al, 2018). The mean score was used as the main dependent measure.…”
Section: School Satisfactionmentioning
confidence: 99%
“…Recently, Perry, Charles, Ncube, and Weiss (2018) There are a number of child, parent and school factors that may contribute to the variability in parent ratings of school satisfaction.…”
mentioning
confidence: 99%